(untitled) (Epidemiology, Biostatistics, and Public Health, 2023)
We are proud to announce the re-starting of the Journal Epidemiology Biostatistics and Public Health (EBPH), made possible thanks to the Milano University Press (MUP), the new publisher of the journal.